Nonlinear optical effects and optomechanical oscillations in hollow Whispering Gallery Mode microresonators: Coexistence, suppression, amplification and route to chaos. Issue 3 (1st February 2023) - Frigenti, Gabriele; Farnesi, Daniele; Roselló-Mechó, Xavier; Barucci, Andrea; Ratto, Fulvio; Delgado-Pinar, Martina; Andrés, Miguel V.; Conti, Gualtiero Nunzi; Soria, Silvia
Abstract: Whispering Gallery Mode (WGM) hollow microcavities turn out to be the site of an extremely rich and complex phenomenological scenario when pumped with a continuous-wave laser source. The coexistence of numerous non-linear and optomechanical effects have been reviewed in this paper. In our previous works we have investigated and described non-linear emissions as the stimulated Brillouin and Raman scattering, the degenerated and non-degenerated Kerr effects, such as four wave mixing (FWM). These effects happened concomitantly to parametric optomechanical oscillations which are the consequence of the radiation pressure. We have confirmed the regenerative oscillation of acoustic eigenmodes of the cavity leading to parametric instabilities and the activation of optomechanical chaotic oscillations. Finally, we have demonstrated that the blue-side excitation of WGM resonances lead to the chaos transition with a spectral evolution depending on the cavity size.